Buckling Analysis of Perforated Hot Rolled Steel Sections - Sagar Dubey, Pradeep Kumar Ghosh, Barkha Verma, Anurag Wahane, Ravi Kumar Khandel (Mathematical Statistician and Engineering Applications, 2022)
Perforated steel plates are frequently used in the construction industry because they are inexpensive, simple to fabricate, have a good strength by weight ratio, and are suitable for a variety of applications. The research present about the effect due to perforation on the buckling resistance of perforated ISMB 400 & ISMB 600 section members are analyzed. The paper deals with three categories i.e., the first case is analyzing the ISMB 400 & 600 section without perforation, the second is analyzing the ISMB 400 section with perforation having equal and unequal spacing and the third case is analyzing ISMB 600 perforated section with equal and unequal spacing. The results show that the deformation increases due to increase in load application the in case of members without perforation and in perforated members’ deformation increase with an increase in the diameter of perforation when they are placed equidistant while the deformation reduces with an increase in diameter of perforation when they are not placed at equidistant.